Penularan COVID-19, Laporan Kasus Seorang Peserta Program Pendidikan Dokter Spesialis Obstetri dan Ginekologi - Lisnawati, Yuyun; Ocviyanti, Dwiana; Wulan, Diyah Septiti (Majalah Kedokteran Indonesia, 2020)
Since COVID-19 first broke out in Jakarta in early March 2020, the infection rate has been slowly but surely increasing. Health workers who work directly to serve patients, including the resident, are vulnerable to infection. The following is a story of a Obstetrics and Gynecology resident who was infected with COVID-19 and managed to recover after going through a period of independent isolation. In March 2020, the resident who at that time served in the Obstetrics polyclinic at a COVID-19 referral hospital in Jakarta, experienced myalgia, fever, headache, sore throat, cough and runny nose. Due to the condition causes PPDS to be rested. Complaints improved within a few days, after taking medication and multivitamin supplementation. One week later, the resident with the other resident and staff conducted a nasopharyngeal swab examination at the hospital, then the samples were sent to Litbangkes for reverse transcription polymerase chain reaction (RT-PCR) examinations against SARS-CoV-2. The results were obtained 20 days later and the resident was declared positive. When the results came out, PPDS who already felt healthy were undergoing rotation in another hospital. Undergo a 2-week self-isolation protocol, nutritious intake, supplementation, exercise, positive thinking and continued prayer. Transmission of COVID-19 may occur while serving patients, social distancing and wearing less awake masks when with PPDS friends, midwives, nurses and staff. The long duration of the RT-PCR swab results makes it difficult for tracing, the risk of widespread transmission and delays in efforts to break the chain of transmission of COVID-19 besides disrupting education rotation.